Measurement of Islamic Bank Capital Capacity as an Assumption Bank in the Resolution Process of Purchasing and Assumption Methods - Aziz, Ahmad; Fatwa, Nur (UI Scholars Hub, 2022)
As a financial institution, Islamic banking certainly has the possibility of problems occurring which will reduce solvency. The emergence of problems in Islamic banking certainly requires authority from the financial authority. One of the authorities that has this authority is the Indonesia Deposit Insurance Corporation through the implementation of the bank's resolution function. The resolution function is carried out by handling and solving bank solvency problems (problem banks), one of the options is the transfer of assets and liabilities. This option can also be referred to as the purchase and assumption (P&A) method. The resolution option for the P&A method is to transfer the assets and liabilities of the troubled bank to the prospective Assuming Bank. In the event that there are Islamic banks experiencing solvency problems, it is necessary to measure other Islamic banks that have the potential to become candidates for Assuming Banks. This measurement uses a quantitative method in the form of a balance sheet implementation (simulation) to determine the impact of the transfer of assets and liabilities on the capital and liquidity of the prospective Assuming Bank. In addition to the simulation mechanism, qualitative methods are also carried out through in-depth interviews to obtain a big picture of the concerns in the resolution process for Islamic banks. Based on the results of the analysis, the resolution process for Islamic banks using the P&A option can be carried out for troubled banks with medium-small asset sizes with Assuming Banks at a higher asset level. This is in line with the bigger the bank's problems, the more it will require the implementation of increasingly complex resolutions.